Age Influences Biomechanical Changes After Participation in an Anterior Cruciate Ligament Injury Prevention Program. Issue 3 (March 2018) - Thompson-Kolesar, Julie A.; Gatewood, Corey T.; Tran, Andrew A.; Silder, Amy; Shultz, Rebecca; Delp, Scott L.; Dragoo, Jason L.
Background: The prevalence of anterior cruciate ligament (ACL) injuries increases during maturation and peaks during late adolescence. Previous studies suggested an age-related association between participation in injury prevention programs and reduction of ACL injury. However, few studies have investigated differences in biomechanical changes after injury prevention programs between preadolescent and adolescent athletes. Purpose/Hypothesis: The purpose was to investigate the influence of age on the effects of the FIFA Medical and Research Centre (F-MARC) 11+ injury prevention warm-up program on differences in biomechanical risk factors for ACL injury between preadolescent and adolescent female soccer players. It was hypothesized that the ACL injury risk factors of knee valgus angle and moment would be greater at baseline but would improve more after training for preadolescent athletes than adolescent athletes. It was further hypothesized that flexor-extensor muscle co-contraction would increase after training for both preadolescent and adolescent athletes. Study Design: Controlled laboratory study. Methods: Institutional Review Board–approved written consent was obtained for 51 preadolescent female athletes aged 10 to 12 years (intervention: n = 28, 11.8 ± 0.8 years; control: n = 23, 11.2 ± 0.6 years) and 43 adolescent female athletes aged 14 to 18 years (intervention: n = 22, 15.9 ± 0.9 years; control: n = 21, 15.7 ± 1.1 years). The intervention groups participated in 15 in-season sessions of the F-MARC 11+ program 2 times per week. Pre- and postseason motion capture data were collected during 4 tasks: preplanned cutting, unanticipated cutting, double-legged jump, and single-legged jump. Lower extremity joint angles and moments were estimated through biomechanical modeling. Knee flexor-extensor muscle co-contraction was estimated from surface electromyography. Results: At baseline, preadolescent athletes displayed greater initial contact and peak knee valgus angles during all activities when compared with the adolescent athletes, but knee valgus moment was not significantly different between age groups. After intervention training, preadolescent athletes improved and decreased their initial contact knee valgus angle (–1.24° ± 0.36°; P = .036) as well as their peak knee valgus moment (–0.57 ± 0.27 percentage body weight × height; P = .033) during the double-legged jump task, as compared with adolescent athletes in the intervention. Compared with adolescent athletes, preadolescent athletes displayed higher weight acceptance flexor-extensor muscle co-contraction at baseline during all activities ( P < .05). After intervention training, preadolescent athletes displayed an increase in precontact flexor-extensor muscle co-contraction during preplanned cutting as compared with adolescent intervention athletes (0.07 ± 0.02 vs –0.30 ± 0.27, respectively; P = .002). Conclusion: The F-MARC 11+ program may be more effective at improving some risk factors for ACL injury among preadolescent female athletes than adolescent athletes, notably by reducing knee valgus angle and moment during a double-legged jump landing. Clinical Relevance: ACL prevention programs may be more effective if administered early in an athlete's career, as younger athletes may be more likely to adapt new biomechanical movement patterns.